1998
DOI: 10.1128/aac.42.6.1524
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of β-Lactamases to β-Lactam Susceptibilities of Susceptible and Multidrug-Resistant Mycobacterium tuberculosis Clinical Isolates

Abstract: The β-lactamases in 154 clinical Mycobacterium tuberculosis strains were studied. Susceptibilities to β-lactam antibiotics, their combination with clavulanate (2:1), and two fluoroquinolones were determined in 24 M. tuberculosisstrains susceptible to antimycobacterial drugs and in nine multiresistant strains. All 154 M. tuberculosis isolates showed a single chromosomal β-lactamase pattern (pI 4.9 and 5.1).M. tuberculosis β-lactamase hydrolyzes cefotaxime with a maximum rate of 22.5 ± 2.19 IU/liter (strain 1382… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Interestingly, according to our results, MDR strains were more susceptible to ␤-lactam antibiotics than M. tuberculosis H37Ra strain. In 1998, Segura et al found that MDR isolates had lower MIC values than other strains in a trial with five different combinations of ␤-lactam antibiotics [13]. Our result agreed with those findings.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, according to our results, MDR strains were more susceptible to ␤-lactam antibiotics than M. tuberculosis H37Ra strain. In 1998, Segura et al found that MDR isolates had lower MIC values than other strains in a trial with five different combinations of ␤-lactam antibiotics [13]. Our result agreed with those findings.…”
Section: Discussionsupporting
confidence: 94%
“…The beta-lactam class of antibiotics has not been used in the treatment of M.tb or other mycobacterial infections as mycobacteria are resistant to these antibiotics and produce betalactamases (Kasik, 1979;Kwon et al, 1995). However, the effectiveness of beta-lactam/beta-lactamase inhibitor combinations has been shown in-vitro for M.tb (Chambers et al, 1995), and also in clinical settings of TB (Chambers et al, 1998;Cynamon et al, 1983;Segura et al, 1998;Sorg and Cynamon, 1987), M. avium (Casal et al, 1987), and M. smegmatis (Yabu et al, 1985). Rv0908 (ctpE), which codes for putative cation transporter, is also present in the same operon.…”
Section: Antibiotic Resistance Operonmentioning
confidence: 97%
“…Still, these genes are expressed weakly if at all in most strains [253], although b-lactamase-mediated resistance to penicillins in this organism has been reported [255]. Mycobacterial resistance to b-lactams is commonplace and generally attributed to the production of b-lactamases by these organisms [256,257]. In Mycobacterium tuberculosis the major enzyme is a class A penicillinase [258], although an enzyme with cephalosporinase activity has also been reported in this organism and, indeed, other mycobacteria [257,258].…”
Section: Gram-positive and Mycobacterial B B-lactamasesmentioning
confidence: 99%